INFLUENCE OF NEBIVOLOL ON A HEART RATE VARIABILITY AT THE PATIENTS RECEIVING ANTHRACYCLINE ANTIBIOTICS - Kalinkina, N.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The anthracycline antibiotics cause infringement of a heart rate variability (HRV). The purpose: to study influences of nebivolol on HRV at the patients receiving anthracycline antibiotics. 73 patients (in the age of 24,5±5,1 years) receiving anthracycline antibiotics which are taking place in a remission on oncohaematological disease and not having pathologies of cardiovascular system were randomized on 2 groups: in 1-st - 37 patients receiving nebivolol in a doze 5 mg 1 times per day, in 2-nd - 36 patients without therapy by β-adrenoblocker. Control group is 30 practically healthy persons. Prior to the beginning therapy by nebivolol and after 6 months the daily monitoring of ECG with an estimation of time and spectral parameters of HRV was carried out. At initial investigation of the patients receiving anthracyclines the decrease of HRV, activation of sympathetic and deppression of parasympathic vegetative nervous system in comparison with the control was observed. At the patients accepting nebivolol through 6 months the increase of HRV, decrease of sympathetic and increase of a parasympathic tone by comparison to the 2-nd group was observed.